1997
DOI: 10.1007/s004420050168
|View full text |Cite
|
Sign up to set email alerts
|

Predation on adult Aphytis parasitoids in the field

Abstract: We report on predation on adult females of the parasitoids Aphytis aonidiae and A. vandenboschi (Hymenoptera: Aphelinidae) foraging in the field. During 89.6 h of observation, we witnessed 18 encounters with predators, 6 of which resulted in parasitoid capture. Three classes of generalist predators attacked Aphytis: spiders (unidentified Salticidae and Thomisidae), workers of the Argentine ant, Linepithema humile, and nymphs of the assassin bug Zelus renardii (Hemiptera: Reduviidae). Although observations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 45 publications
1
87
1
Order By: Relevance
“…When predators are small or highly mobile, for example, direct observation of predation becomes nearly impossible (Hagler et al, 2004). Furthermore, the effort required to detect even a few direct instances of predation, which typically involve multiple species of predators (Heimpel et al, 1997;Rosenheim et al, 1999), makes it difficult to obtain sample sizes large enough for meaningful statistical inference. For these reasons, ecologists rely heavily on PCR-based methods (Symondson, 2002;Sheppard et al, 2004;Foltan et al, 2005;King et al, 2008) and stable isotope analyses (Kelly, 2000;Fiedler et al, 2007;Hood-Nowotny and Knols, 2007) to characterize species interactions and to infer trophic level.…”
Section: Introductionmentioning
confidence: 99%
“…When predators are small or highly mobile, for example, direct observation of predation becomes nearly impossible (Hagler et al, 2004). Furthermore, the effort required to detect even a few direct instances of predation, which typically involve multiple species of predators (Heimpel et al, 1997;Rosenheim et al, 1999), makes it difficult to obtain sample sizes large enough for meaningful statistical inference. For these reasons, ecologists rely heavily on PCR-based methods (Symondson, 2002;Sheppard et al, 2004;Foltan et al, 2005;King et al, 2008) and stable isotope analyses (Kelly, 2000;Fiedler et al, 2007;Hood-Nowotny and Knols, 2007) to characterize species interactions and to infer trophic level.…”
Section: Introductionmentioning
confidence: 99%
“…Actual field mortality rates from any of these factors are largely unknown (Heimpel et al 1997). However, field experiments on Aphytis parasitoids suggest that predation rivals starvation and extreme temperature conditions as sources of mortality (Heimpel et al 1997). We do not expect that the qualitative results of our model will be affected by choosing a life expectancy that is too long.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…In fact, Moreno et al (1987) In previous studies examining the impact of the ants on populations of honeydew producing Hemiptera, lower parasitism rates were reported on plants with ants relative to plants without ants (DeBach et al, 1951;Bartlett, 1961;Itioka & Inoue, 1996b, 1999. Moreover, in the case of non-honeydew producing Hemiptera, several studies showed that ants may disrupt parasitoid activity (DeBach et al, 1951;Flanders, 1958;Murdoch et al, 1995;Heimpel et al, 1997a;Martínez-Ferrer et al, 2003). Recently, a study conducted on Australian citrus revealed that the parasitism of CRS by Encarsia perniciosi (Tower) and Encarsia citrina Craw (Hymenoptera: Aphelinidae) was severely reduced in the presence of the ant Iridomyrmex rufoniger (Lowne) (Dao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…are highly susceptible to ant aggression. In fact, there are studies demonstrating that ants prey upon them in the field (Heimpel et al, 1997a) or disturb them during host-feeding and oviposition (Martínez-Ferrer et al, 2003). Aphytis melinus females spend more than 300 seconds per honeydew feeding bout (Tena et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation